Research Paper: Comparison of Participation of Children With Cerebral Palsy Aged 4 to 6 years in Occupations With Normal Peers - Omid Rostam Zadeh; Malek Amini; Afsoon Hasani Mehraban (University of Social Welfare and Rehabilitation Sciences, 2016)
Objective The participation of children in occupations, such as self-care, home environment, play, leisure, and educational and social environments, is significantly correlated with their health and wellbeing. Therefore, the aim of this study was to compare the children with cerebral palsy (CP) and their normally-developing counterparts in terms of their participation in each area of occupations.   Materials & Methods This case-control study was conducted in 2015 with 50 children (aged 4-6 years) having CP and 50 normally-developing children (aged 4-6 years) in the Tehran city. The participants were chosen by a convenience sampling strategy and examined using the Persian version of Children Participation Questionnaire. The questionnaire was completed by the parents after the necessary explanations. SPSS (version 18) was used for statistical analysis, and independent t-test was used for the comparison. Results The mean ages of children with CP and normally-developing children were 5 years and 5.1 years, respectively. Significant differences (P<0.001) were found in diversity, intensity, enjoyment, assistance, and parent satisfaction with participation in the areas of self-care, home environment, play, leisure, education of children with CP and their peers. However, there was no significant difference in the area of social participation between the two groups (P>0.05). Conclusion The results showed that the children with CP have a lower level of participation in occupations compared to their normally-developing counterparts. One of the reasons for the low participation level of children with CP could be the lack of goal-oriented and occupation-oriented interventions. Thus, this finding will help the healthcare providers to create and develop appropriate  therapeutic and rehabilitation interventions so as to meet the needs of these children and promote their participation level and wellbeing.